The Zoo Switcheroo - Katz, Alan; Lopez, Alex, 1971- (New York, NY : Harper, an imprint of HarperCollins Publishers, 2021)
"Milton Worthy can't wait for his class trip to the city zoo. But little does he know that Noah--part time classroom pet ferret, part time evil mastermind--has escaped and stowed away on his school bus. Good thing that Mrs. Worthy, ace world-saving, member of the super-secret Society of Substitutes, is along for the ride! Will Milton and his super-substitute mom be able to stop the zoo from running completely wild?"
Keywords: Worthy, Milton -- (Fictitious character) -- Juvenile fiction; School field trips -- Juvenile fiction; School children -- Juvenile fiction; Substitute teachers -- Juvenile fiction; Ferrets as pets -- Juvenile fiction; Zoos -- Juvenile fiction; Secret societies -- Juvenile fiction; Action and adventure fiction; Humorous fiction